Gen Z Consumer Behavior and Sustainability Identity in Green Marketing - Rahajeng Cahyaning Putri Cipto (Generate Digital Publishing, 2025)
Objectives: This study aims to analyze how Generation Z internalizes sustainability values as part of their self-identity and how this influences their perception of brands and purchase intentions in the context of green marketing. Research Design & Methods: A qualitative approach with an interpretive phenomenological design was used to understand the subjective experiences and personal meanings associated with Generation Z's concept of sustainability in shaping their self-identity. Findings: The results of this study show that sustainability for Generation Z has become central to their self-identity, reflected through environmentally friendly consumption as an expression of social values and responsibility, reinforced by community and social interactions, and characterized by a critical and skeptical attitude towards brands' sustainability claims, demanding authenticity and consistency from corporations. Implications & Recommendations: These findings have strategic implications for marketers to develop authentic, value-based approaches to sustainability communication. Companies need to focus on real practices and narratives that align with Gen Z's moral identity, rather than merely symbolic strategies. Contribution & Value Added: This research expands the theoretical understanding of the relationship between self-identity, sustainability, and the consumption behavior of the younger generation. This study also provides a relevant empirical framework for the development of identity- and social value-based green marketing strategies.